2004
DOI: 10.1183/09031936.04.00143703
|View full text |Cite
|
Sign up to set email alerts
|

Lung fibroblasts from patients with emphysema show a reduced proliferation rate in culture

Abstract: Emphysema is characterised by a loss of alveolar structure, as reflected in elastic recoil and gas exchange. As fibroblasts play a key role in the maintenance of structure, the current authors hypothesised that their proliferation might be constitutively impaired in lung emphysema.Using explant cultures, lung fibroblasts were obtained from resected lungs of 10 patients with emphysema (median forced expiratory volume in one second (FEV1) 40% predicted) and 10 control patients (FEV1, 95% pred). The doubling time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
107
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 17 publications
14
107
1
3
Order By: Relevance
“…AMSELLEM et al [15] reported a higher percentage of pulmonary vascular endothelial cells stained for senescence markers in COPD patients than in lung healthy controls. This is in line with senescent-type growth characteristics of lung fibroblasts [36]. Furthermore, cellular senescence of pulmonary smooth muscle cells appears to be involved in the pathogenesis of pulmonary hypertension in COPD [37].…”
Section: Discussionsupporting
confidence: 49%
“…AMSELLEM et al [15] reported a higher percentage of pulmonary vascular endothelial cells stained for senescence markers in COPD patients than in lung healthy controls. This is in line with senescent-type growth characteristics of lung fibroblasts [36]. Furthermore, cellular senescence of pulmonary smooth muscle cells appears to be involved in the pathogenesis of pulmonary hypertension in COPD [37].…”
Section: Discussionsupporting
confidence: 49%
“…Gene expression levels of HO‐1, protein expression, and heme oxygenase activity were studied. Senescence was characterized by measuring cumulative population doubling levels (PDLs; Holz et al, 2004), senescence‐associated β‐galactosidase activity (SA β‐gal; Dimri, 2005), and the expression of P‐ATM, p21 by immunofluorescence, and p16 by western blot and real‐time quantitative polymerase chain reaction analysis. Markers of inflammation (IL‐6, IL‐8) were assessed by real‐time quantitative polymerase chain reaction analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In line with this, lung fibroblasts from patients with emphysema exhibit a reduced proliferation rate, lower number of population doublings in serial passaging (Holz et al 2004), and altered growth factor response (Holz et al 2004;Noordhoek et al 2003). In addition, we found an increased staining for senescence-associated beta-galactosidase (β-gal, (Dimri et al 1995)), as well as increased mRNA expression of the insulin-like growth factor-binding proteins (IGFBP)-3 and -rP1 in these cells (Müller et al 2006).…”
Section: Introductionmentioning
confidence: 60%
“…Fibroblasts provide an important part of the lung's structural support and extracellular matrix that is essential for its integrity (Absher 1995). Based on clinical and experimental data it has been hypothesized that the long-term exposure to noxious agents or cigarette smoke, the major cause for emphysema, could result in premature ageing of lung fibroblasts (Holz et al 2004;Nyunoya et al 2006). Such a change in fibroblast phenotype could be responsible for an impaired structural maintenance of the lung and could thereby contribute to the development of emphysema (Nyunoya et al 2006;Tuder et al 2006).…”
Section: Introductionmentioning
confidence: 99%